Diseño de software para el procesamiento y análisis de imágenes biomédicas en 2D utilizando librerías ITK - Fernando Martínez Santa; Sergio Alejandro Rojas Barbosa; Wilmer Antonio Blanco Riaño (Tecnura, 2010)
The libraries ITK (InsightSegmentation and RegistrationToolkit) make up one open source, cross platform, providing a system with a wide range of software tools for analyzing and processing images. ITK employs leading-edge algorithms for the registration and segmentation of multidimensional data, algorithms aimed at the exploration and manipulation of different characteristics of images, allowing different functions to interact with images such as thresholding, edge detection, gradient, curvature and other filters image, which are responsible for particular highlight in an image depending on theapplication you want to provide. ITKUD application was implemented to make use of some of these algorithms and also to create a completely free software environment allowing for portability, ie, the compilation on any system that supports C++.